A fully soft, self-powered vibration sensor by laser direct writing. (1st December 2022) - Luo, Huayu; Lu, Yuyao; Xu, Yuhong; Yang, Geng; Cui, Songya; Han, Dong; Zhou, Qitao; Ouyang, Xiaoping; Yang, Huayong; Cheng, Tinghai; Xu, Kaichen
Abstract: Soft electronics are comprised of stretchable and user-friendly components that mechanically conform to complex surfaces and epidermis, extending their applicability over commercial electronics. Vibration sensors that detect operation conditions of common motions generally rely on rigid materials or tedious fabrications. Here, a fully soft self-powered vibration sensor (SSVS) engineered by laser-assisted fabrication is proposed. Different from its rigid counterparts, the device is constructed with entirely ductile materials including a liquid metal kernel and an elastic shell. Furthermore, laser direct writing elaborates intricate patterns and functional surfaces of SSVS in a rapid and mask-free manner. A ubiquitous IR laser combined with an origami-inspired transfer creates arbitrary out-of-plane electrodes on soft media, while a pulsed UV laser judiciously tunes nonstick microstructures to the liquid metal droplet. To demonstrate the capability on curved surfaces, the SSVS is interfaced with an exhaust silencer of an air compressor and detects failures of screw connection. Additionally, a cap reinforced by SSVS with wireless transmission is devised for motion monitoring, which effectively distinguishes slip from walking, jumping and running. This work affords promising routes toward monitoring complex machinery and remote guardianship for the vulnerable populations. Graphical Abstract: ga1 Highlights: The proposed self-powered vibration sensor is composed of fully soft materials. Laser direct writing creates conductive media as well as textured non-adhesive surfaces to the droplet vibration kernel. Case studies for the sensor show its potential to work on curved machines and track the intensity of human activities.